Writing method in the thematic interpretation of the Holy Quran - Al Deek, Mohammed Yousef (Arab Journal for Sciences and Research Publishing, 2017)
This research deals with the writing method in the objective interpretation of the Qur’an, which is based on the rooting of Qur’anic guidances for related studies, and the writing method in which it continues to write in scientific research taking into account the steps and procedures of this approach in terms of the choice of the topic as an issue outside the text without contenting the words in the Qur’an. Where the plan is written in the light of the Qur’anic verses and titles, and the arrangement of the verses as much as possible, especially in order to show the canceler and the canceled from the Qur’anic verses, taking into account the reasons for descending of the verses, with reference to interpretations of different types with a focus on procedural steps by harmonious linking Step, source and method of use, linking it to reality as much as possible in order to get a precise picture of the subject of research in the light of Qur’anic purposes.